Analysis of performance development of Purun craftsman in palm district, Banjarbaru City to improve skills in an effort to improve product quality - Dewi Ariefahnoor; Yudi Permana; Abdul Kadir (Institute of Computer Science (IOCS), 2024)
Human resources have an important role in an organization, so improving performance is an important need in all activities of the purun craftsmen of Palm Banjarbaru Village. This research aims to have the skills of purun craftsmen so that they can produce products in the form of purun crafts that are of good quality, have innovative, diverse products, and are timely in their completion. The research method used is the Systematic Literature Review (SLR) method. The result of the research is that regular skill development can help increase knowledge and the ability of craftsmen to complete their crafts can also improve the performance of craftsmen. Skilled craftsmen also need education or coaching so that the results of the craft have aesthetic value and besides that the skills to train patients to produce quality products.